Mir-21 expression and its correlation with demographics, subtypes, and tumour suppressor genes; PTEN and PDCD4 in breast cancer tissues in Malaysia - Wong, Sharon Rachel; Chong, Pei Pei; Mohd Islahuddin, Mohd Tamrin; Baghawi, Anita; Gew, Lai Ti; Singaram, Nallammai; Lee, Sau Har (Kare Publishing, 2024)
Objectives: Despite extensive research in breast cancer (BC) genomics, most studies are from Western countries, which do not reflect the multi-ethnic make-up of Malaysia. Hence, microribonucleic acid-21 (miRNA-21), which is known to be an oncogenic stimulator of BC will be investigated by comparing its expression between breast tumour tissues and normal adjacent tissues excised from 67 BC patients, ethnic groups, age groups distribution, neo-adjuvant chemotherapy (NAC) treated and untreated patients, as well as BC subtypes. Methods: Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to measure the distribution of miR-21 expression in the paired BC tissues. The expression of the tumour suppressors; PTEN and PDCD4 was also investigated via RT-qPCR and Western Blot for its gene and protein expressions. Results: The results only showed the significance of miR-21 and PTEN expression between the normal adjacent tissues and BC tissues (p<0.05). Additionally, there was a lack of correlation between gene expression of miR-21 against PTEN and PDCD4. Protein expression analysis did not show a significant difference in tumour suppressor proteins; PTEN and PDCD4 expression in both tissue types. Conclusion: miR-21 has a notable presence in BC and is a suitable biomarker to be evaluated further in patients of all ethnicities and age groups.